2013
DOI: 10.1007/s12224-013-9174-0
|View full text |Cite
|
Sign up to set email alerts
|

Species Richness Pattern along Altitudinal Gradient in Central European Beech Forests

Abstract: The unimodal species richness-altitude distribution pattern seems to be universal. To investigate the validity of this phenomenon in homogeneous substrate and vegetation conditions, we sampled beech-dominated forests in five volcanic mountain ranges in the Western Carpathians. European beech (Fagus sylvatica L.) formed monodominant closed-canopy stands at altitudes from 300 to 1,200 m. Along this gradient, the influence of beech on understory plant species richness was expected to be strong and uniform. The sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 55 publications
1
8
0
1
Order By: Relevance
“…Recently, various studies were conducted-especially on plants-to assess how species richness of different lifeforms is influenced by elevation (Akhtar and Bergmeier 2015;Zhang et al 2016;Xu et al 2017). In some rare cases, researchers found the same relationship between elevation and species richness (unimodal or monotonic) for all the studied lifeforms (Sánchez-González and López-Mata 2005;Hemp 2006;Hrivnák et al 2014;Xu et al 2017) but, more often, this relationship differs between the lifeforms (Zhao et al 2004;Grytnes et al 2006;Ren et al 2006;Gairola et al 2008;Akhtar and Bergmeier 2015;Zhang et al 2016;Nanda et al 2018). Some of these works have been performed in small elevation gradients and most of them in temperate climates.…”
Section: The Elevational Pattern Of Species Richness Depends On the Smentioning
confidence: 82%
“…Recently, various studies were conducted-especially on plants-to assess how species richness of different lifeforms is influenced by elevation (Akhtar and Bergmeier 2015;Zhang et al 2016;Xu et al 2017). In some rare cases, researchers found the same relationship between elevation and species richness (unimodal or monotonic) for all the studied lifeforms (Sánchez-González and López-Mata 2005;Hemp 2006;Hrivnák et al 2014;Xu et al 2017) but, more often, this relationship differs between the lifeforms (Zhao et al 2004;Grytnes et al 2006;Ren et al 2006;Gairola et al 2008;Akhtar and Bergmeier 2015;Zhang et al 2016;Nanda et al 2018). Some of these works have been performed in small elevation gradients and most of them in temperate climates.…”
Section: The Elevational Pattern Of Species Richness Depends On the Smentioning
confidence: 82%
“…It is known that species richness is negatively related to the competition between species [29]. Low species richness indicates a higher competition for resources, which is conducive to the development and accumulation of above-ground biomass [30]. Therefore, for the effective soil water use and sustainable development of eco-economy, the optimum growth period of alfalfa pasture should be maintained at four years in the Tibetan Plateau, and it should be rotated to another crop after the fourth year of plantation.…”
Section: Discussionmentioning
confidence: 99%
“…The unimodal response appears to be universal and other linear trends can be addressed to habitat-related biases such as restricted length of analysed gradient. It has been also found that size and composition of local species pool (Hrivnák et al 2014) and environmental conditions expressed through the effect of several often covarying factors vary along the altitudinal gradient (Rahbek 2005). The positive effect of the short altitudinal gradient (330-805 m) revealed in our study presumably reflects better growth conditions at higher altitudes (submontane zone) of this region, where both increasing precipitation and prevalence of only slightly acidic and neutral soil substrates jointly support higher herb-layer productivity.…”
Section: Herb-layer Vascular Plantsmentioning
confidence: 96%
“…Vegetation patterns are also controlled by an altitudinal gradient which does not represent an ecological factor per se. Its impact is ultimately caused by abiotic forces (i.e., changes in a set of site-specific conditions) and stochastic processes (Hrivnák et al 2014).…”
Section: Introductionmentioning
confidence: 99%